KAJIAN SINTAKSIS PADA NOVEL SANG PENCURI WARNA KARYA YERSITA - Cahyo Hasanudin (Jurnal Pendidikan Edutama, 2018)
AbstractThis study aims to describe the form of 1) phrase, 2, clause, and 3) sentence on novel of Sang Pencuri Warna by Yersita. This research is a qualitative descriptive study. Data collection using documentation techniques by applying strategis read, listen, and take note. Data analysis using content analysis Miles and Huberman. The result of the research shows 1) the existence of phrase form based on the relationship between the element and the core element of the word type, 2) the existence of positive and negative clauses, 3) the existence of the phrase based on pronunciation, grammatical structure, function or content, element, arrangement, presentation style (rhetoric), and the subject. Keywords: Phrase, Clause, Sentence, Novel AbstrakPenelitian ini bertujuan mendeskrispikan bentuk  1) frasa, 2, Klausa, dan 3) kalimat pada Novel Sang Pencuri Warna karya Yersita. Penelitian ini merupakan penelitian deskripstf kualitatif. Pengumpulan data menggunakan teknik dokumentasi dengan menerapkan strategi baca-cimak-catat. Analisis data menggunakan content analysis Miles dan Huberman. Hasil penelitian menunjukkan 1) adanya bentuk frasa berdasar hubungan antar unsur dan unsur inti jenis kata, 2) adanya bentuk klausa positif dan negatif, 3) adanya kalimat berdasar pengucapan, struktur gramatikal, fungsi atau isi, unsur, susunan, gaya penyajian (retorik), dan subjek Kata kunci: Frasa, Klausa, Sentence, Novel